Sistem Informasi Point of Sales (POS) Pada CV Sedulur Teknik dengan Teknik Menggunakan Metode Agile - Hemdani Rahendra Herlianto; Muhammad Chaidir Alam (DPPM Universitas Pelita Bangsa, 2023)
Processing of goods and sales data on CV Sedulur Teknik still uses manual methods, to find out the goods sold and sales transactions must be calculated by means of a bookkeeping system. The calculation of sales turnover must be calculated using a calculation tool such as a calculator because there is no sales system so that some incoming sales data does not match which has an impact on the difference in nominal sales figures and this manual method makes work longer. So a point of sales system was created on CV Sedulur Teknik in order to assist in the transaction process. This sales system uses PHP (Hypertext Preprocessor) as the programming language used, and Mysql as the database used and Xampp to connect the database to the website. The method used is the agile scrum pattern method, scrum itself is a software that is used agile to stand in a team, additional product processes and software development that focuses on speed and is carried out by realizing the final result.